Teaching ICT to Pre-Service Teachers: Experiences and Reflections (LEARNing Landscapes, 2014)
Information and Communication Technologies (ICT) are increasingly used in education settings, and graduates from teacher education programs are expected to have adequate knowledge and skills to integrate ICT in their teaching. Inspired by some studies that report cases about pre-service teachers’ ICT-related learning in different countries in Asia, this article presents, in case-study format, the experimentations carried out regarding the teaching of ICT as part of the curriculum to pre-service teachers in a teacher education program in Ontario, Canada. The aim is to share with instructors and researchers in teacher education institutions and programs what we can learn from our experiences, and how we can use these experiences to improve our practice.
Keywords: Information and Communication Technologies (ICT); teacher education; practice; experience; case study